1981
DOI: 10.1002/ajh.2830110207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endotoxin on arachidonic acid release and thromboxane B2 production by human platelets

Abstract: Plasma thromboxane A2, which is elevated during endotoxemia, has previously been shown to be a major factor contributing to the mortality and morbidity that occurs in endotoxin shock in the experimental animal. Using a minimal dose of Escherichia coli endotoxin (1 microgram/ml), we have demonstrated that the preincubation of human platelets with endotoxin induces changes in platelet arachidonic acid release and the subsequent conversion of the released arachidonic acid to thromboxane B2, and stable end product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…There are, however, several mechanisms by which the oral infections may be linked with the development of vascular diseases. Components of causative bacteria of oral infections, especially gramnegative bacterial LPS, may have effects promoting atherosclerosis (Hirsch et al 1964, Morrison & Ulevitch 1978, Sakaguchi 1982, and affect the blood coagulation, the function of platelets and prostaglandin synthesis (Momson & Ulevitch 1978, Stuart 1981, which all are important in thrombus formation. The systemic effects of recurrent transient bacteremias associated with poor oral health are not well-known.…”
Section: Vascular Diseases and Oral Infectionsmentioning
confidence: 99%
“…There are, however, several mechanisms by which the oral infections may be linked with the development of vascular diseases. Components of causative bacteria of oral infections, especially gramnegative bacterial LPS, may have effects promoting atherosclerosis (Hirsch et al 1964, Morrison & Ulevitch 1978, Sakaguchi 1982, and affect the blood coagulation, the function of platelets and prostaglandin synthesis (Momson & Ulevitch 1978, Stuart 1981, which all are important in thrombus formation. The systemic effects of recurrent transient bacteremias associated with poor oral health are not well-known.…”
Section: Vascular Diseases and Oral Infectionsmentioning
confidence: 99%
“…Also, it is reported that components of causative bacteria of oral infections, particularly lipopolysaccharide, may promote atherosclerosis and affect blood coagulation, the function of platelets, and prostaglandin synthesis. [16][17][18] Bacteremia caused by non-surgical periodontal treatments rarely affects healthy people because the bacteria that gain access to the bloodstream are rapidly removed by phagocytic cells, such as Kupffer cells in the liver. 19 However, in patients at potential increased risk, bacteremia from periodontal procedures could be implicated in the development of infective endocarditis, 20 prosthetic joint infection, 21 and a variety of other distant site infections.…”
mentioning
confidence: 99%
“…Incubation of platelets, neutrophils and macrophages with endotoxin in vitro enhances the response of these cells to other stimuli (Stuart 1981;Forehand et al 1989;Burrell 1990;Aida and Pabst 1990). Neutrophils have enhanced shape change response and greater ability to release superoxide anion (Forehand et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils have enhanced shape change response and greater ability to release superoxide anion (Forehand et al 1989). macrophages and platelets increase agonist receptor numbers and affinity, and release a greater amount of arachidonic acid and its metabolites after exposure to endotoxin (Stuart 1981;Aderem et al 1986). The mechanisms by which endotoxin enhances these responses has not been determined but similar mechanisms may result in the enhanced PAF-induced platelet aggregation identified after iv endotoxin administration in this study.…”
Section: Discussionmentioning
confidence: 99%